Antithrombotic choice in blunt cerebrovascular injuries: Experience at a tertiary trauma center, systematic review, and meta-analysis. Issue 1 (July 2021) - Ku, Jerry C.; Priola, Stefano M.; Mathieu, Francois; Taslimi, Shervin; Pasarikovski, Christopher R.; Zeiler, Frederick A.; Machnowska, Matylda; Nathens, Avery; Yang, Victor X.D.; da Costa, Leodante
Abstract : BACKGROUND: Blunt cerebrovascular injuries (BCVIs) may occur following trauma and lead to ischemic stroke if untreated. Antithrombotic therapy decreases this risk; however, the optimal agent has yet to be determined in this population. The aim of this study was to compare the risk-benefit profile of antiplatelet (AP) versus anticoagulant (AC) therapy in rates of ischemic stroke and hemorrhagic complications in BCVI patients. METHODS: We performed a retrospective review of BCVI patients at our tertiary care Trauma hospital from 2010 to 2015, and a systematic review and meta-analysis of the literature. The OVID Medline, Embase, Web of Science, and Cochrane Library databases were searched from inception to September 16, 2019. References of included publications were searched manually for other relevant articles. The search was limited to articles in humans, in patients 18 years or older, and in English. Studies that reported treatment-stratified clinical outcomes following AP or AC treatment in BCVI patients were included. Exclusion criteria included case reports, case series with n < 5, review articles, conference abstracts, animal studies, and non–peer-reviewed publications. Data were extracted from each study independently by two reviewers, including study design, country of origin, sex and age of patients, Injury Severity Score, Biffl grade, type of treatment, ischemic stroke rate, and hemorrhage rate. Pooled estimates using odds ratio (OR) were combined using a random-effects model using a Mantel-Hanzel weighting. The main outcome of interest was rate of ischemic stroke due to BCVI, and the secondary outcome was hemorrhage rate based on AC or AP treatment. RESULTS: In total, there were 2044 BCVI patients, as reported in the 22 studies in combination with our institutional data. The stroke rate was not significantly different between the two treatment groups (OR, 1.27; 95% confidence interval, 0.40–3.99); however, the hemorrhage rate was decreased in AP versus AC treated groups (OR, 0.38; 95% confidence interval, 0.15–1.00). CONCLUSION: Based on this meta-analysis, both AC and AP seem similarly effective in preventing ischemic stroke, but AP is better tolerated in the trauma population. This suggests that AP therapy may be preferred, but this should be further assessed with prospective randomized trials. LEVEL OF EVIDENCE: Review article, level II. Abstract : Supplemental digital content is available in the text.